Transforming Growth Factor-β Induces Interleukin-6 Secretion from Human Ligamentum Flavum–Derived Cells through Partial Activation of p38 and p44/42 Mitogen-Activated Protein Kinases - Yuta Goto; Kenji Kato; Kiyoshi Yagi; Yohei Kawaguchi; Hiroki Yonezu; Tomoko Koshimae; Yuko Waguri-Nagaya; Hideki Murakami; Nobuyuki Suzuki (Asian Spine Journal, 2023)
Study Design This experimental study was performed using human ligamentum flavum–derived cells (HFCs). Purpose To investigate the intracellular signaling mechanism of interleukin-6 (IL-6) secretion in transforming growth factor-β (TGF-β)-stimulated HFCs. Overview of Literature Lumbar spinal stenosis (LSS) is a prevalent disease among the elderly, characterized by debilitating pain in the lower extremities. Although the number of patients with LSS has increased in recent years, the underlying pathomechanism remains unclear. Clinical examinations typically rely on magnetic resonance imaging to diagnose patients, revealing ligamentum flavum hypertrophy. Some studies have suggested an association between ligamentum flavum hypertrophy and inflammation/fibrosis, and expression of TGF-β and IL-6 has been observed in surgically obtained ligamentum flavum samples. However, direct evidence linking TGF-β and IL-6 expression in HFCs is lacking. Methods HFCs were obtained from patients with LSS who had undergone decompression surgery. The cells were stimulated with TGF-β and pretreated with either the p38 mitogen-activated protein (MAP) kinase inhibitor SB203580 or the p44/42 MAP kinase inhibitor FR180204. IL-6 secretion in the cell culture medium and IL-6 messenger RNA (mRNA) expression levels were analyzed using an enzyme-linked immunoassay and real-time polymerase chain reaction, respectively. Results TGF-β administration resulted in a dose- and time-dependent stimulation of IL-6 release. Treatment with SB203580 and FR180204 markedly suppressed TGF-β–induced IL-6 secretion from HFCs. Moreover, these inhibitors suppressed IL-6 mRNA expression in response to TGF-β stimulation. Conclusions Our findings indicate that TGF-β induces IL-6 protein secretion and gene expression in HFCs through the activation of p38 or p44/42 MAP kinases. These results suggest a potential association between IL-6–mediated inflammatory response and tissue hypertrophy in LSS, and we provide insights into molecular targets for therapeutic interventions targeting LSS-related inflammation through our analysis of the MAP kinase pathway using HFCs.